Taxing Financial Transactions : Issues and Evidence - Matheson, Thornton (IMF Working Papers; Working Paper ;, 2011)
In reaction to the recent financial crisis, increased attention has recently been given to financial transaction taxes (FTTs) as a means of (1) raising revenue for a variety of possible purposes and/or (2) helping to curb financial market excesses. This paper reviews existing theory and evidence on the efficacy of an FTT in fulfilling those tasks, on its potential impact, and on key issues to be faced in designing taxes of this kind.